Atomic force microscopy under defined hydrodynamic conditions: Three-dimensional flow calculations applied to the dissolution of salicylic acid - Wilkins, S; Suarez, M; Hong, Q; Coles, B; Compton, R; Tranter, G; Firmin, D (2000)
The kinetics of the dissolution of salicylic acid in aqueous solutions is studied using in situ atomic force microscopy, using a novel liquid flow cell for which the full three-dimensional flow pattern is known. This allows the interpretation of dissolution rate in terms of an interfacial reaction mechanism, with excellent agreement between the theoretically predicted and the experimental results. The use of a three-dimensional simulation to obtain the flow velocities enables accurate prediction over a much wider range of flow rates than is possible using a simpler two-dimensional model for the flow pattern. The dissolution of the (110) face of salicylic acid in the presence of water and aqueous solutions containing sodium chloride has been studied as a function of flow rate and is found to be consistent with a model combining a constant rate of dissolution with some redeposition having a first-order dependence on the surface concentration [SA]0, with the flux J = kf - kb[SA]0. The parameters for kf are found to be 2.04 × 10-8, 1.65 × 10-8, and 8.85 × 10-9 mol cm-2 s-1 for dissolution in water and 0.1 M and 1 M sodium chloride, respectively, at a cell temperature of 21°C.